IDENTIFIKASI FAKTOR DETERMINAN RESIDIVISME - Iqrak Sulhin; Yogo Tri Hendiarto (Jurnal Kriminologi Indonesia, 2011)
Recidivism are repetion of criminal conduct by individuals on his/her life time. The Instrumen Penelitian Masyarakat or Litmas which been used by correctional system can only provide qualitative information regarding any offender to be use by judge in order to give sentence. Therefore, the need for quantitative determinant analysis to identify inmates re-offending risk factor emerge. The method use by this research gathering is survey method with inmates from Class I A Cipinang Correctional Facility. The process to analyse and identify risk determinant of an inmate for re-offending can give benefit for rehabilitation process given to the inmates. The findings shonw that drugs and/or alcohol abuse, and also emotional or personality problems are factors that correlate to criminal records